Women’s perception of urban insecurity in the Monterrey metropolitan area during COVID-19 = Percepción femenina de la inseguridad urbana en el área metropolitana de Monterrey en tiempos de COVID-19 = A percepção das mulheres sobre a insegurança urbana na área metropolitana de Monterrey em tempos de COVID-19 - Cantú-Martínez, Pedro César (Revista Criminalidad, 2023)
The purpose of this paper it to explore women’s perception of urban insecurity prevailing during the COVID-19 pandemic in the Monterrey metropolitan area (MMA) in Mexico. In recent decades, large cities have grown and with them, so has crime increased. As a result, the issue of urban insecurity has become important, particularly during this COVID-19 pandemic. For this purpose, a cross-sectional, descriptive, non-probabilistic study was conducted involving 69 women aged 18 to 58, with Universidad Autónoma de Nuevo León being taken as the sample frame. Our findings show that 74% of the participants indicate that urban safety near their homes, ranges fair to very bad, while 81% feel the same about safety near their workplaces. Ninety- three per cent say that crime has increased. Meanwhile, 55% say that the situation has affected their quality of life severely to very severely, denoting the MAM population’s transition from one of social well-being to one of vulnerability, which has been further aggravated by the health contingency.